2020
DOI: 10.3390/molecules25122876
|View full text |Cite
|
Sign up to set email alerts
|

Methylpiperidinopyrazole Attenuates Estrogen-Induced Mitochondrial Energy Production and Subsequent Osteoblast Maturation via an Estrogen Receptor Alpha-Dependent Mechanism

Abstract: An estrogen deficiency is the main cause of osteoporosis in postmenopausal women. In bone remodeling, estrogen receptors (ERs) can mediate estrogen-transducing signals. Methylpiperidinopyrazole (MPP) is a highly specific antagonist of ER-alpha (ERα). This study was designed to evaluate the effects of MPP on estrogen-induced energy production, subsequent osteoblast maturation, and the possible mechanisms. Exposure of primary osteoblasts isolated from neonatal rat calvarias to MPP did not affect cell morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In the current study, serum PVT1 levels were found to increase gradually over time after treatment for the fracture patients. It is known that the healing of fractures requires the proliferation of osteoblasts [ 29 ]. Considering the remarkable changes of serum PVT1 levels during fracture healing, its role in osteoblasts proliferation and apoptosis was further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, serum PVT1 levels were found to increase gradually over time after treatment for the fracture patients. It is known that the healing of fractures requires the proliferation of osteoblasts [ 29 ]. Considering the remarkable changes of serum PVT1 levels during fracture healing, its role in osteoblasts proliferation and apoptosis was further explored.…”
Section: Discussionmentioning
confidence: 99%
“…For every experiment, naringin with a purity > 95% was freshly prepared by dissolving it in dimethyl sulfoxide (DMSO). Human U-2 OS cells were exposed to 1, 10, and 100 μM naringin for 6, 12, and 24 h. MPP is a specific inhibitor of ERα . To inhibit activation of ERα, MPP, procured from Gibco-BRL, was prepared by dissolving it in DMSO.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In our previous study, administration of naringin, one of the bioactive ingredients in the water extract of Gusuibu, expanded trabecular bone numbers, bone strength, and bone mass in ovariectomized rats . An increase in ALP activity, a well-characterized biomarker of osteoblasts, corresponds to osteoblast activation and maturation. , ERα, compared to ERβ, plays a more significant role to mediate estrogen- and genistein-induced ATP production, osteogenesis, and bone formation. , Recently, we demonstrated that methylpiperidinopyrazole (MPP) can be used as a specific inhibitor of ERα to suppress estrogen-induced ATP synthesis and osteoblast maturation . However, how ERα contributes to naringin-induced improvements in bone healing and bone mass are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Morphologies and survival of human and mouse drug-sensitive and -resistant glioblastoma cells were analyzed according to a previously described method [ 27 ]. Drug-resistant glioblastoma cells (10 4 cells/well) were seeded in 12-well tissue culture plates overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxic conditions in drug-resistant U87 MG-R and GL261-R glioblastoma cells were created by inducing HIF-1α [27]. Drug-resistant glioblastoma cells (10 4 cells/well) were seeded in 12-well tissue culture plates overnight.…”
Section: Creation Of Hypoxic Conditions and Drug Treatmentmentioning
confidence: 99%